2008
DOI: 10.1099/vir.0.2008/002501-0
|View full text |Cite
|
Sign up to set email alerts
|

The essential and non-essential genes of Bovine herpesvirus 1

Abstract: Bovine herpesvirus 1 (BoHV-1) is an economically important pathogen of cattle associated with respiratory and reproductive disease. To further develop BoHV-1 as a vaccine vector, a study was conducted to identify the essential and non-essential genes required for in vitro viability. Random-insertion mutagenesis utilizing a Tn5 transposition system and targeted gene deletion were employed to construct gene disruption and gene deletion libraries, respectively, of an infectious clone of BoHV-1. Transposon inserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 37 publications
(47 reference statements)
1
46
0
Order By: Relevance
“…For gD, we have shown that the earlier expression of the protein in BHV1-⌬U L 47-infected cells correlated with significantly elevated gD mRNA levels at very early stages of infection. Unlike VP22, gD is essential for the viability of BHV-1 in cell culture (42), suggesting that the low gD protein levels could account at least in part for the U L 47 deletion mutant growth defect. We have shown that whereas gD mRNA synthesis and stability in BHV1-⌬U L 47-infected cells remained normal, the stability of the protein was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For gD, we have shown that the earlier expression of the protein in BHV1-⌬U L 47-infected cells correlated with significantly elevated gD mRNA levels at very early stages of infection. Unlike VP22, gD is essential for the viability of BHV-1 in cell culture (42), suggesting that the low gD protein levels could account at least in part for the U L 47 deletion mutant growth defect. We have shown that whereas gD mRNA synthesis and stability in BHV1-⌬U L 47-infected cells remained normal, the stability of the protein was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike VP22, which is not required for BHV-1 replication in cell culture (28,42), the U S 6 gene product, gD, was shown to be essential (42). Hence, the altered expression of gD could account to some extent for the U L 47-null virus growth defect.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…The complete removal of the mini-F vector by homologous recombination has been limited to laborious cotransfection experiments or to BAC constructs with restricted stability in bacteria (Strive et al, 2007;Wagner et al, 1999;Yu et al, 2002). Alternatively, the vector elements can be flanked by recognition sites for site-specific recombinases, which leave behind only one small recognition sequence (Adler et al, 2000(Adler et al, , 2001Chang & Barry, 2003;Smith & Enquist, 2000;Strive et al, 2006;Tanaka et al, 2003;Zhao et al, 2008 Horsburgh et al, 1999a, b;Nagel et al, 2008;Saeki et al, 1998;Stravropoulos & Strathdee, 1998;Tanaka et al, 2003Meseda et al, 2004Nagaike et al, 2004Tischer et al, 2007;Wussow et al, 2009;Yoshii et al, 2007;Zhang et al, 2007Brazeau et al, 2011Gray et al, 2011Smith & Enquist, 1999Mahony et al, 2002Robinson et al, 2008 …”
Section: Generation Of Recombinant Large Dna Virusesmentioning
confidence: 99%
“…PrV was cloned as a BAC and used for pathogenesis studies in vivo (Smith & Enquist, 1999Fuchs et al, 2009;Kopp et al, 2004]. Additional varicellovirus BACs of various animals have been studied in vitro and in vivo: Bovine herpesvirus type 1 (BHV-1; Gabev et al, 2009;Mahony et al, 2002;Robinson et al, 2008;Trapp et al, 2003), EHV-1 (Goodman et al, 2007;Yao et al, 2003), canine herpesvirus (CHV; Strive et al, 2006), and feline herpesvirus type 1 (FHV-1; Costes et al, 2006;Richter et el., 2009;Tai et al, 2010). Moreover, BACs exist for the mardiviruses Marek's disease virus (MDV) and herpesvirus of turkeys (HVT) (Baigent et al, 2006;Petherbridge et al, 2003;Schumacher et al, 2000;Zhao et al, 2008).…”
Section: Functional Mutagenesis Of Specific Viral Bacsmentioning
confidence: 99%